A systematic review of intervention thresholds based on FRAX. Issue 1 (December 2016) - Kanis, John; Harvey, Nicholas; Cooper, Cyrus; Johansson, Helena; Odén, Anders; McCloskey, Eugene
Abstract Summary This systematic review identified assessment guidelines for osteoporosis that incorporate FRAX. The rationale for intervention thresholds is given in a minority of papers. Intervention thresholds (fixed or age-dependent) need to be country-specific. Introduction In most assessment guidelines, treatment for osteoporosis is recommended in individuals with prior fragility fractures, especially fractures at spine and hip. However, for those without prior fractures, the intervention thresholds can be derived using different methods. The aim of this report was to undertake a systematic review of the available information on the use of FRAX® in assessment guidelines, in particular the setting of thresholds and their validation. Methods We identified 120 guidelines or academic papers that incorporated FRAX of which 38 provided no clear statement on how the fracture probabilities derived are to be used in decision-making in clinical practice. The remainder recommended a fixed intervention threshold (n  = 58), most commonly as a component of more complex guidance (e.g. bone mineral density (BMD) thresholds) or an age-dependent threshold (n  = 22). Two guidelines have adopted both age-dependent and fixed thresholds. Results Fixed probability thresholds have ranged from 4 to 20 % for a major fracture and 1.3–5 % for hip fracture. More than one half (39) of the 58 publications identified utilised a threshold probability of 20 % for a major osteoporotic fracture, many of which also mention a hip fracture probability of 3 % as an alternative intervention threshold. In nearly all instances, no rationale is provided other than that this was the threshold used by the National Osteoporosis Foundation of the USA. Where undertaken, fixed probability thresholds have been determined from tests of discrimination (Hong Kong), health economic assessment (USA, Switzerland), to match the prevalence of osteoporosis (China) or to align with pre-existing guidelines or reimbursement criteria (Japan, Poland). Age-dependent intervention thresholds, first developed by the National Osteoporosis Guideline Group (NOGG), are based on the rationale that if a woman with a prior fragility fracture is eligible for treatment, then, at any given age, a man or woman with the same fracture probability but in the absence of a previous fracture (i.e. at the 'fracture threshold') should also be eligible. Under current NOGG guidelines, based on age-dependent probability thresholds, inequalities in access to therapy arise especially at older ages (≥70 years) depending on the presence or absence of a prior fracture. An alternative threshold using a hybrid model reduces this disparity. Conclusion The use of FRAX (fixed or age-dependent thresholds) as the gateway to assessment identifies individuals at high risk more effectively than the use of BMD. However, the setting of intervention thresholds needs to be country-specific.